Language Learning Strategies Employed by Successful and Less Successful Learners - Chairina Nasir; Yunisrina Qismullah Yusuf; Raihan Zulfarlia (Proceedings of AICS - Social Sciences, 2016)
This study investigated the language learning strategies used by successful and less successful learners in the first grade of a senior high school in Banda Aceh. Both groups of learners were categorized based on their scores on an English test. A number of 20 successful and 20 less successful first grade students were then selected as the respondents. A questionnaire was used to identify language learning strategies used by both groups of these learners. The questionnaire was adapted from Oxford (1990), which consisted 30 items related to six categories of language learning strategies: memory, cognitive, compensation, metacognitive, affective, and social. This data were then analyzed by using the independent sample t-test. The findings revealed that there was a significant difference between language learning strategies used by successful and less successful learners. The successful learners were found to use the language learning strategies more frequently than less successful learners. Thus, both groups of learners obtained the highest scores in the metacognitive strategy; this implies that these learners understood how to manage their own learning. The lowest scores obtained by the successful learners were in the affective strategies, whilst the less successful learners were in the memory strategies. Other strategies (compensation, cognitive and social) were also used by both groups of these learners. Hence, less successful learners did not use all of the language learning strategies very often; this is what affected them to become less effective in language learning. Therefore, it is suggested that teachers should train the less successful learners to apply more language learning strategies in their learning to improve their academic achievement.